Fresno March and Rally Against War in El Salvador - Watkins, Howard::::::::: (1981)
March going under Belmont underpass at H Street; Leroy Cordova and Joanne Cordova holding Banner "No Vietnam in El Salvador"; Scott Williams, Marilyn Williams; Jesse Avila carrying daughter